Investigating The Role of Information Technology, Motivation and Competence on Goverment Employee Performance - Rayyan Aqila Praditya; Rafie Zaidan Prayuda; Agus Purwanto (Journal of Industrial Engineering & Management Research, 2023)
Purpose: The research aims to identify and analyze the effect of information technology on government employee performance, the effect of motivation on government employee performance and the influence of competence on government employee performance Methods: This research was conducted to test the hypothesis proposed by using quantitative methods. This type of research is research with a quantitative approach and the nature of the research. Population is a group or group of research objects from which data will be collected. The whole or totality of the object under study whose characteristics are suspected or estimated. The research design used a survey research that took a sample from one population and used a questionnaire as the main data collection tool. The research was carried out in government offices. The population in the study, namely all government employees, totaled 680 people. The sampling technique used in this study is simple random sampling. Data analysis using structural equation modelling (SEM) partial least square (PLS) and use software SmartPLS 3.0 Results: From the research results the influence of Information technology Mastery variables on performance is obtained t count 4.836 > t table 1.96 and a significant value t 0.05 > 0.00, indicating that information technology has a positive and significant influence on performance, From the research results the effect of the motivational variable on performance is obtained t count 8.401 > t table 1.96 and a significant value 0.00 <0.05, indicating that motivation has a positive and significant influence on performance, From the research results the effect of the competency variable on performance is obtained t count 4.904 <t table 1.96 and a significant value 0.00 <0.05, indicating that competence has a positive and significant influence on performance. Conclusion: Based on the description and results of the analysis shown previously, it can be concluded as follows: The results show that information technology has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance Information Technology has a positive and significant effect towards career development, then this needs to be maintained and improved again in order to maximize performance